Insect Conservation Biology 2007
DOI: 10.1079/9781845932541.0001
|View full text |Cite
|
Sign up to set email alerts
|

Insect conservation in temperate biomes: issues, progress and prospects.

Abstract: The interests and priorities for insect conservation in the better-documented and generally less species-rich northern temperate regions and in the more poorly understood, but more diverse biomes of southern temperate regions are described, largely focusing on experiences in the UK and Australia. Conservation threats to temperate insects (habitat change, impact of introduced species, impacts of biological control agents on nontarget species, extinction cascades, and insidious threats) are briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Our present study highlights that insect taxa may respond differently to management intensity and local and landscape factors, and that regional characteristics can influence their responses. This conclusion must be taken into consideration when developing conservation‐oriented agri‐environmental schemes and a community‐based approach to insect conservation (Stewart & New, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our present study highlights that insect taxa may respond differently to management intensity and local and landscape factors, and that regional characteristics can influence their responses. This conclusion must be taken into consideration when developing conservation‐oriented agri‐environmental schemes and a community‐based approach to insect conservation (Stewart & New, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that assemblages of insect communities can vary according to vegetation (e.g. Botha, Siebert, & Van den Berg, ; Stewart & New, ). In addition, it has been shown that, in insectivorous bats, jaw size and muscle strength are considerably more important in smaller than in larger species and, thus, have a significant effect on diet (Ghazali, Moratelli, & Dzeverin, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the course of the literature study for the environmental risk assessment for N. typhlocybae it was noticed that, with just a few exceptions, potential risks of the release of exotic invertebrates for the control of pests have not been routinely assessed in pre-release evaluations, and that screening information on the impact on non-target organisms is required in only a few countries (van Lenteren et al 2006;Stewart et al 2007;Bale 2011). to mitigate the risk associated with the introduction of exotic natural enemies of plant pests in a new geographic region, the threat to the native fauna, in particular, needs to be assessed before a new species is released (Hoddle 2004;Bélanger and Lucas 2011;Maisonhaute and Lucas 2011).…”
Section: Discussionmentioning
confidence: 99%